Efficacy of Egg Parasite, Trichogramma Spp. in Parasitising the Eggs of the Teak Skeletonizer, Pyrausta machaeralis Walker (Lepidoptera : Pyralidae) - Patil, B. V.; Thontadarya, T. S. (Indian Forester, 1984)
Three exotic Trichcgramma species, namly T. pkcal, T. braslliimsis and T. evanescen when released against the teak skeletonizer, Pyrousta machaeralis Wlk. in teak plantation area during October survived upto 105, 90 and 60 days respectively, indicating their possible establlshment and survival capacity when released in large numbers.